2018
DOI: 10.1002/jper.18-0545
|View full text |Cite
|
Sign up to set email alerts
|

Smoking confounds the periodontal diagnostics using saliva biomarkers

Abstract: Background Smoking is a risk factor for periodontal disease because of its complex impact on the inflammatory response in the periodontium. We investigated the effect of smoking on salivary periodontal biomarkers, matrix metalloproteinase (MMP)‐8, MMP‐9, tissue inhibitor of metalloproteinase (TIMP)‐1 and myeloperoxidase (MPO). Methods Saliva biomarkers were analyzed in the Parogene population (n = 480) comprising a random cohort of patients that have undergone coronary angiography and oral examination. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Biomarker analysis is dependent on many factors, like the collection system, the individual salivary flow rate (66), stimulated or unstimulated sampling, time of sampling, centrifugation and processing, the storage of samples, and the detection method. Furthermore, aggravating factors for periodontitis such as smoking (67)(68)(69) or stress, but also gender have a locally or systemically influence on the secretion of biomarkers into saliva (66,70,71). It was also shown that blood contamination of saliva samples could have an impact on biomarker levels (72).…”
Section: Influencing Factors On Salivary Biomarkersmentioning
confidence: 99%
“…Biomarker analysis is dependent on many factors, like the collection system, the individual salivary flow rate (66), stimulated or unstimulated sampling, time of sampling, centrifugation and processing, the storage of samples, and the detection method. Furthermore, aggravating factors for periodontitis such as smoking (67)(68)(69) or stress, but also gender have a locally or systemically influence on the secretion of biomarkers into saliva (66,70,71). It was also shown that blood contamination of saliva samples could have an impact on biomarker levels (72).…”
Section: Influencing Factors On Salivary Biomarkersmentioning
confidence: 99%
“…The strong relation between TIMPs and MMPs suggests that TIMPs might potentially serve as a biomarker to diagnose periodontitis and monitor disease progression in oral fluids. 12 , 13 Of the four types of TIMPs identified in humans, TIMP‐1, an inhibitor of MMP‐9, has most often been associated with periodontal disease. However, so far the diagnostic value of TIMP‐1 in periodontal disease has not been systematically reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the simultaneous presence of CVD on the one hand and periodontitis on the other hand can be a real explanation for the deterioration of endothelial function due to high levels of MPO. In this regard, recent research has shown that the treatment of periodontitis has significantly reduced the systemic levels of MPO in patients with coronary disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several reports demonstrated that increased hs-CRP levels in serum can facilitate the increment of MPO levels in serum in several diseases in humans [23,[35][36][37][38]. In accordance with the results of our study, several studies have been demonstrated that situations which may cause an increase of oxidative stress, such as CVD and periodontal disease, cause the high release of CRP, which in turn, can arouse the production of MPO in saliva and serum in order to defend tissue damage determined by oxidative stress condition [36].…”
Section: Discussionmentioning
confidence: 99%